Emancipazionismo e femminismo tra le pagine de L’Alleanza (1906-1911) - Tiziana Pironi (Laboratoire Italien)
This essay examines the annual issues of the weekly magazine L’Alleanza, which was founded in Pavia by Carmela Baricelli, a teacher from Cremona, whose aim was to use the magazine to promote a gender alliance among women, beyond different political parties. Thanks to her resourcefulness and self-initiative, the magazine lasted longer than other similar publications of the time, achieving a good national circulation, as it officially put itself forward as a “liaison body” for the various pro-suffrage committees. As this research points out, L’Alleanza was not only an important forum on which women could discuss the emerging emancipationist issues of the time, but also a training and self-education tool for its readers who, in many cases, wrote articles, short news items and stories, at the same time learning rules and procedures for participating in congresses and assemblies. The pages of the journal reveal how an entire generation of women dealt with the broad spectrum of themes associated with the “Feminist issue”: not only the leading figures of the time (Maria Montessori, Teresa Labriola, Emilia Mariani and others), but also those less well known, about whom we have very little biographical information, but who nevertheless made a fundamental contribution to the debate generated in the journal.